Body image struggles and breast cancer care: an under-recognized and undertreated issue with important implications for all patients. (May 2014) - DeSnyder, Sarah M; Teo, Irene; Fingeret, Michelle Cororve
SUMMARY : Body image encompasses the relationship between perceptions, cognitions, behaviors and emotions regarding the body and its functions. Breast cancer treatment can have a profound impact on body image, with body image issues occurring throughout diagnosis, treatment and survivorship. Despite this, a potential disconnect exists between breast cancer care providers and patients with respect to understanding and addressing body image difficulties. This article provides an overview of body image issues related to breast cancer treatment and offers recommendations that will enable healthcare providers to assist patients who are struggling with body image issues. More emphasis must be placed on the importance of body image as a means of improving the quality of care for all breast cancer patients.